Enhancing at Crosswalks and Sidewalks: A Case Study of Kathmandu Metropolitan City - Shahi, Divya; Shahi, Thusitha Chandani (Journal on Transportation System and Engineering, 2025)
This study evaluates pedestrian safety and walkability in Kathmandu Metropolitan City by developing and applying two indices: the Sidewalk Condition Index (SCI) and the Crosswalk Condition Index (CCI). Through a comprehensive literature review, 16 sidewalk and 11 crosswalk attributes were identified. Expert consultations using the Analytical Hierarchy Process (AHP) provided relative weights for each attribute, while a user perception survey (n = 420) captured the experiences of pedestrians. This combined approach ensured both technical priorities and community perspectives were reflected in the assessment. Six urban road sections with the highest pedestrian fatality records were analyzed. Results show that effective signal control (weight = 0.50), zebra crossings (0.47), and sidewalk lighting (0.38) are the most influential factors. SCI values ranged from –0.04 to 1.10, and CCI values from –0.08 to 0.62, identifying S4 (Gongabu – Sarkaridhara) as the least safe section and S6 (Narayan Gopal Chowk – T.U. Teaching Hospital) as the most walkable. The study recommends prioritizing improvements such as enhanced signal timing with pedestrian phases, installation of zebra crossings and refuge islands at high-risk intersections, and regular sidewalk maintenance to ensure continuity and safety. These findings offer a transferable framework for enhancing pedestrian infrastructure in Kathmandu and other similar South Asian urban contexts.